Secular Examination of Spirituality-Prosociality Association - Dong, Mengchen (Archive for the psychology of religion, 2017)
Religious beliefs in Chinese cultural background, especially in Chinese secular society, have rarely been systematically investigated. The nonreligious-based population in China endorses certain supernatural beliefs or has related transcendent experience, even though they usually claim themselves as non-believers. Therefore, the current research examined the spirituality-prosociality association in Chinese secular background, demonstrating how spiritual connection with the transcendence related to individual secular social life. A total of 440 Chinese participants completed our questionnaires in three survey studies. The results showed that: 1) for the nonreligious-based population in China, spirituality was positively connected with personal prosocial trait, prosocial attitude, and prosocial behavior; 2) the prosocial trait of compassionate love partially mediated the association between spirituality and daily prosocial expenses on time and money; and 3) personal emphasis on moral principles such as ultimate justice beliefs partially mediated the association between spirituality and interpersonal altruism in organizational settings. Limitations and future directions were discussed.